Prevalence of refractive error among patient population attending UiTM optometry clinic / Nuryasmin Nordin - Nordin, Nuryasmin (2016)
Purpose: The study purposes were to identify the distribution of patient population attending UiTM Vision Care Optometry Clinic by their demographic data and to explore the distribution pattern of refractive status and the prevalence of refractive error among them. Methods: A retrospective study was done and patient record files were retrieved among patient population who attending in this clinic since year 2011 until 2015 by simple random method. Data was analysed and presented in percentage, frequency, mean and standard deviation by using the descriptive analysis. Results: Almost third quarter of the patient population who presenting in this clinic were students and majority of them were female students. Myopia (49.6%) has the higher prevalence of refractive error among them. Meanwhile, the hyperopic and presbyopic patients were rarely seen and were uncommon refractive error in this clinic since the percentage both of it showed the lowest. Adolescents ranging from age 10 to 19 years of age presented the highest prevalence of myopia. The prevalence rates of myopia in female population were observed to be not much different from males. Myopic patients had with-the-rule astigmatism showed the highest frequency among astigmatism groups. The overall mean spherical equivalent was -1.22±2.33 Conclusion: In this study, it showed that myopia was the commonest refractive error among patient population who presenting in this clinic.